Immigrant Pavement Ant Tetramorium immigrans Santschi (Insecta: Hymenoptera: Formicidae) - Miles Maxcer; Jason Williams; Andrea Lucky (EDIS)
The immigrant pavement ant, Tetramorium immigrans Santschi is one of the most commonly encountered ants in the United States. The first introduction into the United States occurred from Europe in the beginning of the 19th century. Since then, the species has become well established and is prevalent in urban areas in the northern U.S. and parts of Canada. While the presence of immigrant pavement ants in the U.S. has been acknowledged for decades, the extent of its invasiveness and severity as a pest are not well characterized.